Development and Application of the Placebo Response Model in Clinical Trials for Primary Sjögren’s Syndrome - Wang, ZHI-Zhou; Zheng, Qing-Shan; Liu, Hong-Xia; Li, Lu-Jin (Frontiers in Immunology, 2021)
Objective. This study aimed to develop a placebo response model for pharmaceutical clinical trials of primary Sjogren's syndrome,and to quantitatively analyze the distribution and related factors influencing the placebo response to further optimize the design of clinical trials and evaluate the results of single-arm clinical trials. Methods. Public databases, including PubMed, Embase, and Cochrane Library were searched for reports on randomized placebo-controlled trials for Sjögren's syndrome which used the change from baseline in ESSDAI score as the primary outcome. The model-based meta-analysis method was used to evaluate the time course and the related influencing factors of the placebo response for ESSDAI in such clinical trials. A virtual placebo control group was constructed based on the final placebo response model to determine the treatment efficacy of belimumab and cyclosporine A for primary Sjögren's syndrome in a single-arm study. Results. A total of 12 studies involving 450 subjects were included in the analysis. The established model described the time-course characteristics of the changes in ESSDAI score from the baseline in the 48 weeks placebo group. We found that the onset time of placebo response was approximately 12 weeks, and its efficacy plateaued at 48 weeks. The baseline ESSDAI score had a significant effect on the maximum value of the placebo response; the maximum value of the placebo response decreased by 0.552 for every 1 score rise in the baseline ESSDAI score. The efficacy of belimumab and cyclosporine A in the single-arm trial was comparable to that of the placebo response at the same baseline; no significant therapeutic advantage was observed. Conclusion. The placebo response model established in this study could provide a basis for designing clinical trials for primary Sjogren's syndrome in the future. It may also provide a reliable external efficacy control standard for single-arm clinical trials.